What Would You Do Without Your Smartphone? Adolescents’ Social Media Usage, Locus of Control, and Loneliness as a Predictor of Nomophobia - Yıldız Durak, Hatice (Addicta: The Turkish Journal on Addictions, 2018)
Smartphones, with their constantly evolving features, facilitate instant communication and help individuals stay connected with the world at all times. This can lead people to become addicted to their smartphones. In particular, behaviors that indicate smartphone addiction in adolescents have become increasingly prevalent. The most important of these behaviors is nomophobic behavior. This study aims to determine adolescents’ smartphone usage and levels of nomophobia, and to examine the variables related to nomophobia. The study group of this research, which uses the relational survey model, consisted of 786 students studying in the 7th and 8th grades of a middle school in the fall semester of 2016. A personal information form and four data collection tools were used in this study. Frequency, percentage, mean, standard deviation, correlation, and multiple linear regression analyses were used to analyze the quantitative data. In this study, social media addiction was found to most positively correlate with adolescents’ nomophobic behavior levels, and locus of control was found to have the lowest positive correlation with nomophobic behavior levels. In the conclusion of the study, further recommendations have been made. To